Length-Weight Relationships and Condition of Gerreids (Pisces: Gerreidae) from the Parangipettai Waters (SE coast of India) - Sivashanthini, K. (My University, 2008)
The parameters of length-weight relationships were obtained for male, female and unsexed Gerres filamentosus and G. abbreviatus from the Parangipettai waters (SE coast of India). Covariance analysis for length–weight relationships of males, females and unsexed of both species revealed that there was no significant variation among males, females and unsexed (P>0.05) and hence common formulae of W = 0.00676* TL3.285 and W = 0.00910 * TL3.178 were derived for G. filamentosus and G. abbreviatus, respectively. The relative condition of both fishes showed seasonal variations. In females, low relativecondition values were observed during October-February for both species. The highest mean values of average condition factor were recorded from 160 to 185 mm TL in G. filamentosus and from 170 to 195 mm in G. abbreviatus.